Effect of Body Mass Index on Sitting Pressure Distribution on Seat Cushion - Hu, Lingling; Tor, Onder; Duan, Pengzheng; Zhang, Jilei; Yu, Xiaohong (Springer International Publishing, 2018)
The pressure distribution between a seat and people is a very important index in the assessment of sitting discomfort for seat cushion. However, limited research has been found for the relationship between pressure distribution and anthropometric dimensions, especially for Body Mass Index (BMI) of users with different sizes. Effects of BMI ranges (underweight, normal and obese) and cushion hardness (medium, firm, extra firm and wood board) were the factors investigated in this study. The results indicated that the normal participant had a higher comfort degree than the obese and underweight participants. The obese participant preferred the extra firm foam cushion compared to normal participants who preferred the medium foam cushion.
Keywords: 2. Zero hunger; 16. Peace & justice